EXAMINATION OF THE VARIATION OF MTA POWER WHEN WORKING WITH OIL ANAMEGATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
One of the main indicators of internal combustion engines, tractors and the machine-tractor unit as a whole it's the power. It can change in the process of operation and there comes a time when subsequent use is inadmissible or inexpedient. In such a state, it is appropriate to apply technology to improve this indicator and reduce the fuel or lubricant consumption.The power parameter of an agricultural power machine is essential to achieve high productivity with low operating costs with minimal environmental pollution. The monitoring of changing the power is generally carried out by equipment unbearable and unnecessary for the farmer. The possibility for determining the power of the tractor fitted with the working machine by means of a standard brake performance device is a suitable option for monitoring the technical condition of the machinery. In this way, timely detection of defects and prevention of serious consequences for the engine.Worldwide, various technological options have been developed to improve the power of engines without the need for their disassembly. One of these technological options is the fitting of anamegators (additives) in very small quantities to the engine lubricant oil.In this article is made the experiments to evaluating of the variation of the power performance of a diesel tractor engine treated with anamegators as part of a machine-tractor unit. The acceleration and speed of the machine-tractor unit is recorded through a specialized device ENERGOTEST SM4. On this basis of the experimental results obtained, the driving force and power of the tractor from the machine-tractor unit has been determined by theoretical relationships.